Research on Precise Flow Control and Anti-interference Performance of Load Sensitive Multi-way Valve with After-valve Compensation. Issue 1 (1st January 2023) - Ye, Yuan; Fu, Ling; Junhua, Zhang; Wang, Wei; Yanbin, Liu; Wu, Bin
Abstract: Regarding a load-sensitive system with after-valve compensation, in the case of a single action or composite action, theoretically, the flow of each channel neither varies with the load pressure of this channel, nor is it affected by the flow of other channels, and the anti-interference performance is good. In fact, due to the influence of factors such as the flow passage of the valve body, the matching between the pressure compensation valve and the main spool, its flow control and anti-interference performance are difficult to achieve good results, which has a great impact on the synchronization, rapid action impact and micro motion characteristics of the main engine of construction machinery. This paper studies the simplification and analysis of the system pressure drop diagram, the matching characteristics between the pressure compensation valve and the main valve, accurate modeling and simulation technology, solves the problems of flow fine control and anti-interference performance, improves the flow control accuracy of a single action and compound action, and enhances the anti-interference performance. The real vehicle test shows that the self-developed multi-way valve for compensating for load sensitivity behind the valve is installed on the 6T small excavation. The initial position of the excavator's track is aligned along a straight line. After the test runs for 20 meters, the track offset is measured. The fast forward offset is only 20mm, and the slow forward offset is only 7mm.